influência da adição de diferentes sais em pastas de cimento portland para cimentação de poços de petróleo - Costa, Bruno Leonardo de Sena (2013)
One of the great challenges at present time related with the materials area concerns of products and processes for use in petroleum industry, more precisely related to the Pre-salt area. Progresses were reached in the last years allowing the drilling of the salt layer, with the time reduction for drilling and larger success at the end. For the oil wells companies the preponderant factor is the technology, however, in spite of the progress, a series of challenges is still susceptible to solutions and one of them refers to the slurries preparation for cementing in those areas. Inside of this context, this study had for objective to analyze the influence of the salts NaCl, KCl, CaSO4 and MgSO4 in strength and chemical structure of the hydrated products. As methodology, they were prepared and analyzed cement slurries with varied concentrations of these salts that are commonly found in the saline formations. The salts concentrations used in formulations of the slurries were of 5%, 15% and 30%. The slurries were formulated with specific weight of 15,8 lb / gal and the cement used was Class G. Strength tests were accomplished in samples cured by 24 hours and 28 days. Also were realized crystallographic characterization (XRD) and morphologic (SEM). In agreement with the presented results, it is observed that the largest resistance values are attributed to the slurries with concentration of 15%. There was reduction of the strength values of the slurries formulated with concentration of 30%. Through the characterization microstructural it was possible to note the salts influence in the main cement hydrated products